2015
DOI: 10.1371/journal.pone.0136246
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Clinical Significance of MAD2L1 and BUB1, Genes Frequently Appearing in Expression Signatures for Breast Cancer Prognosis

Abstract: To investigate the biologic relevance and clinical implication of genes involved in multiple gene expression signatures for breast cancer prognosis, we identified 16 published gene expression signatures, and selected two genes, MAD2L1 and BUB1. These genes appeared in 5 signatures and were involved in cell-cycle regulation. We analyzed the expression of these genes in relation to tumor features and disease outcomes. In vitro experiments were also performed in two breast cancer cell lines, MDA-MB-231 and MDA-MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 53 publications
5
56
0
Order By: Relevance
“…There were reports suggesting that microarray data from different platforms did not correlate well [22, 23]. We had the same impression when we compared gene expression signatures generated by different microarray platforms for breast cancer prognosis and found little overlap in genes across different signatures [24]. This phenomenon led us to think that our previous results need to be validated by other microarray platforms.…”
Section: Discussionmentioning
confidence: 70%
“…There were reports suggesting that microarray data from different platforms did not correlate well [22, 23]. We had the same impression when we compared gene expression signatures generated by different microarray platforms for breast cancer prognosis and found little overlap in genes across different signatures [24]. This phenomenon led us to think that our previous results need to be validated by other microarray platforms.…”
Section: Discussionmentioning
confidence: 70%
“…MAD2L1 protein is a component of the mitotic spindle assembly checkpoint and inhibits the onset of the anaphase by sequestering CDC20 until all chromosomes are aligned at the metaphase plate (41). It has been reported that MAD2L1 is highly expressed in patients with lung cancer (42), and furthermore, MAD2L1 may have the potential to be used as a diagnostic marker and therapeutic target in breast cancer (41). In addition, high intratumoral MAD2L1 levels may lead to reduced recurrence-free survival rates of patients with cancer (41).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MAD2L1 is highly expressed in patients with lung cancer (42), and furthermore, MAD2L1 may have the potential to be used as a diagnostic marker and therapeutic target in breast cancer (41). In addition, high intratumoral MAD2L1 levels may lead to reduced recurrence-free survival rates of patients with cancer (41).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Abal et al 50 , they mentioned that APC inactivation is associated with abnormal mitosis and concomitant BUB1B/MAD2L1 up-regulation. However, the overexpression of these two genes was correlated with tumor metastasis and poor prognosis of patients with breast cancer 51 . Its expression is amplified in colon cancer as well.…”
Section: Discussionmentioning
confidence: 99%